Exercise and sleep - Review and future directions - Sunao Uchida; Kohei Shioda; Yuko Morita; Chie Kubota; Masashi Ganeko; Noriko Takeda (Japanese Society of Physical Fitness and Sports Medicine, 2012)
This review focuses on the effects of exercise on sleep. In its early days, sleep research largely focused on central nervous system (CNS) physiology using standardized tabulations of several sleep-specific landmark electroencephalogram (EEG) waveforms. This method has enabled the observation and inspection of numerous uninterrupted sleep phenomena. Research on the effects of exercise on sleep began, in the 1960's, with a focus primarily on sleep related EEG changes (CNS sleep). Those early studies only found small effects of exercise on sleep. However, more recent sleep research has explored not only CNS functioning, but somatic physiology as well. Sleep should be affected by daytime exercise, as physical activity alters circadian pacemaker, endocrine, autonomic nervous system (ANS) and other somatic functions. Since endocrinological, metabolic and autonomic changes can be measured during sleep, it should be possible to assess exercise effects on somatic physiology in addition to CNS sleep quality, evaluated by standard polysomnographic (PSG) techniques. Additional measures of somatic physiology have provided enough evidence to conclude that the auto-regulatory, global regulation of sleep is not the exclusive domain of the CNS, but is heavily influenced by inputs from the rest of the body.